Efektivitas Pendayagunaan Dana Zakat Terhadap Pengembangan Program Pemberdayaan Ekonomi Masyarakat Pada Zona Madina Dompet Dhuafa - Rifqi Hattan; Nining Nurhasanah; Firmansyah Firmansyah (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2018)
This research is to analyze the effectiveness of the utilization of zakat funds to the development of community economic empowerment program at Zona Madina Dompet Dhuafa. This research uses quantitative approach with explanatory and explorative research type. Data collection through field observation, interviews, and documentation studies. The data analysis used the calculation of effectiveness ratio and Wilcoxon Signed Rank Test to analyze the effect of the program on the condition of beneficiary community between before and after program. The results of this study show the utilization of zakat funds to the community economic empowerment program at Zona Madina Dompet Dhuafa from 2015 to 2017 amounted to 99.92%. So that the utilization of zakat funds to the community economic empowerment program in Zona Madina Dompet Dhuafa has been very effective, because the effectiveness ratio shows lebiih besar dari 90%. Then based on statistical test nonparametrik Wilcoxon showed that the community economic empowerment program positively affect the changing economic conditions of the beneficiary community program.